Solitary Spinal Epidural Metastasis from Prostatic Small Cell Carcinoma - Kyung Ryeol Lee; Young Hee Maeng (Case Reports in Radiology)
Solitary, spinal epidural metastasis (SEM) that is not related to vertebral metastasis is very rare. And solitary SEM from prostatic cancer is rarely found in previously published reports. However, it is clinically significant due to the possibility of neurologic dysfunction, and it can be assessed by MRI. In this report, we show a case of solitary SEM arising from prostatic small cell carcinoma detected by MRI.